Incidences and characteristics of monkey-related injuries among locals and tourists in Mueng District, Lopburi Province, 2013 - 2017 - Juttuporn, Anothai; Hengpraprom, Sarunya; Rattananupong, Thanapoom (Chulalongkorn Medical Journal, 2020)
Background: Conflicts between monkeys and humans are increasing, mainly because of urbanization and deforestation. Mueng district of Lopburi Province is one of the greatest conflict areas in Thailand, where public health concerns of zoonoses transmission from monkey - bites and scratches are high. Currently, there is no epidemiological research of monkey-related injuries in Thailand. Objectives: The purposes of this study were to determine the incidence of monkey-related injuries and investigate the trends and characteristics of the injured cases in Mueng District, Lopburi Province, in 2013 - 2017. Methods: A cross - sectional analytical study was conducted to compare monkey-related injuries and investigate the incidences between locals, Thai, and foreign tourists by collecting secondary data from medical records in 3 hospitals in the study area. The cumulative incidences were used to calculate relative risk between the tourists and the locals. The characteristics of the injury cases are presented by frequency and percentage. Results: Yearly incidences of locals, Thais, and foreign tourists were in the ranges of 9.16 - 18.33, 190.16 - 379.13, and 254.07 – 736.91 per 100,000 population, respectively. The trend of injury was remarkably higher in foreign tourists. Recently, in 2016 - 2017, Thai and foreign tourists had relative risks of injury estimated as 20 and 40 times compared to that of the locals, respectively. Time, place and circumstance of injury, and wound site suggested monkey provisioning with food as the main risk factor of monkey-related injuries. Conclusion: The incidences of monkey-related injuries was highest in foreign tourists, followed by Thai tourists. Preventive measures should primarily focus on the tourists, such as training on safety behaviors with monkey, promoting pre- and post-exposure prophylaxis, and providing safeguards, warning signs, and first aids stations at monkey provisioning sites.